Integrating mixed crop–livestock systems in Ethiopia’s highlands: A systems synthesis from focus group discussions - Ayehu, Getachew Tesfaye; Abera, Wuletawu (2025)
Mixed crop–livestock systems (MCLS) underpin livelihoods, food security, and resilience in Ethiopia’s highlands, yet their performance depends on complex interactions among crops, livestock, land, and institutions. This study synthesizes evidence from focus group discussions with researchers and extension experts in Enset-based systems (Lemo and Doyogena) and cereal-based systems (Basona Werana). Using a systems thinking and DPSIR (Drivers, Pressures, States, Impacts, and Responses) framework, it characterizes components, resource flows, synergies, and trade-offs shaping productivity and sustainability. Results show that competing claims over biomass, nutrients, and land strongly influence outcomes, while functional diversity, especially Enset enhances resilience. The study identifies key leverage points for integrated management, highlighting the need for coordinated, system-oriented interventions to improve productivity, resilience, and environmental sustainability.